Monks’ Role accordance with Studying Social Work - Tasunurak, Phrakhrupiboonphatthanapimol Panyawaro (Wishing Journal Review, 2023)
Monks’ Role accordance with Studying Social Work accordance with Buddhist Institute was the main point and important for Thai society continue and lasting. All the most of Thai population were Buddhism faith and respectful on Buddhist like their ancestors. Therefore, monks were been leadership for taking and teaching Buddha’s speech for them. So that, monks were regarded to the important for disciples who treatment and propagation for Buddhism to be progressive and stable for next generation until nowadays. They were not reforming the best Buddhist but should be reform some Buddhist activity 6 plus 1 part by committees’ monks’ organization which the top for Thai governor about Buddhist administrator by 6 parts as follow, 1) Government 2) Educational 3) Education for Housing 4) Propagation 5) Unities 6) Unity Housing then one more was Development center of Buddhmomtol for the Buddhist world.